Leadership Behaviour in High- Performing Government Boys Secondary Schools in Quetta: A Grounded Theory Analysis (Journal of Education and Educational Development, 2020)
The performance of schools is highly dependent on the leadership of school heads, and, flexible leaders accelerate school performance. The purpose of this qualitative study was to examine leadership behavior in selected boys’ secondary schools that are performing well. Based on multiple-case study design, four high-performing schools from Quetta were selected as sites. Collectively, four principals, four vice-principals and purposively selected sixteen teachers constituted the sample of the study. The data were collected from semi-structured interviews. For the data analysis, the study relied on grounded theory approach through open-coding, axial coding and selective coding. The findings revealed that the school principals possessed different leadership behaviors, such as changeoriented, relation-oriented and task-oriented behaviors. Moreover, different leadership behaviors contribute to school performance. The implications of the study, recommendations and suggestion are also discussed.